Dependence of CsK2Sb photocathode performance on the quality of graphene substrate film. Issue 1 (1st January 2023) - Guo, L; Goto, K; Yamaguchi, H; Yamamoto, M; Takashima, Y
Abstract: A high-performance photocathode is required to advanced accelerators and electron microscopes. In particular, the CsK2 Sb photocathode is of interest because it has features such as low emittance, excitability with visible light, and high quantum efficiency (QE). Generally, the CsK2 Sb photocathode is produced by depositing a cathode element on a substrate, so that the cathode performance strongly depends on the surface condition of the substrate. We have found graphene as reusable substrate, which has the property of being chemically inactive. In this study, graphene film quality dependence of CsK2 Sb photocathode performance was evaluated. Specifically, CsK2 Sb photocathode was deposited using different quality graphene film substrates and their QE values and uniformity were compared. The quality of graphene films was analyzed using X-ray Photoelectron Spectroscopy (XPS) and X-ray Absorption Spectroscopy (XAS). We found that the graphene film can be cleaned by heating at 500 deg. The QE of the cathode on a good quality graphene film was higher and more uniform than that on a poor quality graphene film.